A philosophic contribution to the ecological public opinion - Contreras, Fernando R. (Javnost (Ljubljana), 2011)
This article demonstrates that the cultural layer of public opinion on environment is based, basically in theology and in political philosophy. However, postmodernist culture has engendered an environmentalist paradigm with new properties inspired by biocentrism (conservation, contamination, extinction) in consumption (recycling, reforestation), a perspective of relativism and a hermeneutic view of mass media's information. The aim of thisessay is to evaluate whether public opinion processes may vary from the norm when new social discourses are studied. From the new findings we have assumed that, currently, public discourse on the environment is easily assimilable through its proximity to other ideological discourses.
Keywords: javno mnenje; ecology; ekologija; environmental protection; varstvo okolja; filozofija kulture